Polycyclization decorated organoboron emitters with hetero[8]helicenes electronic structure for highly‐efficient and stable narrowband circularly polarized electroluminescence - Chenglong Li; Jianping Zhou; Hengyi Dai; Meng Li; Dongdong Zhang; Lian Duan (InfoMat)
Abstract Multiresonance organoboron helicenes are promising narrowband circularly polarized luminescence (CPL) emitters, which, however, still face formidable challenges to balance a large luminescence dissymmetry factor (glum) and a high luminescence efficiency. Here, two pairs of organoboron enantiomers (P/M‐BN[8]H‐ICz and P/M‐BN[8]H‐BO) with the same hetero[8]helicene geometric structures are developed through polycyclization decoration. We find that it is the helicity of helicene electronic structures rather than the geometrical one that determines the molecular dissymmetry property as a larger electronic helicity could enhance the electron‐orbital coupling of the helicene structure. Therefore, P/M‐BN[8]H‐BO who possesses a hetero[8]helicene electronic structure realizes a nearly one‐order‐of‐magnitude higher glum (+2.75/−2.52 × 10−3) and a higher photoluminescence quantum yield (PLQY) of 99% compared with P/M‐BN[8]H‐ICz bearing only a hetero[6]helicene electronic distribution structure (glum of only +2.41/−2.37 × 10−4 and PLQY of 95%). Moreover, BN[8]H‐BO exhibits a narrowband green emission peaking at 538 nm with a full‐width at half‐maxima of merely 34 nm, narrower than most multiresonance CPL helicenes. The corresponding organic light‐emitting diodes simultaneously realize a high external quantum efficiency of 31.7%, an electroluminescence dissymmetry factors (gEL) of +5.23/−5.07 × 10−3, and an extremely long LT95 (time to 95% of the initial luminance) of over 731 h at an initial luminance of 1000 cd m–2.